Illegal Market Governance and Organized Crime Groups’ Resilience: a Study of The Sinaloa Cartel - Pereda, Valentin (The British journal of criminology, 2024)
Since its emergence in the early 1990s, the Sinaloa Cartel has effectively surmounted all challenges to its existence, while, simultaneously, successfully developing its illegal ventures in Mexico and beyond. Based on evidence from the accounts of witnesses who testified in the prosecution of Joaquin Guzmán Loera (also known as El Chapo), one of the Sinaloa Cartel’s most prominent figures, we argue that this OCG’s resilience partially derives from the illegal governance practices it has implemented in the criminal markets in which it operates. In particular, we contend that the Sinaloa Cartel’s reliance on four types of illegal governance have been pivotal in promoting its capacity to weather adversity, namely: (1) judicial, (2) financial, (3) political and (4) regulatory governance.